An Investigation into The Adoption and Usage of Electronic Banking Systems - Shaline Tumushabe (Uganda Christian University, 2023)
The study examined an investigation into the adoption and usage of electronic banking systems. Specific objectives of the study were, to examine the factors influencing customers adoption of E-banking services, to identify and analyze the challenges associated with E-banking systems and to find out the relationship between electronic banking and customer satisfaction in commercial banks. The study used a descriptive cross-sectional design using both qualitative and quantitative approach to collect data from a sample of 59 respondents. Questionnaires were used to collect the data. Quantitative data was analyzed using measurement of central tendency . The study found that customers highly value the convenience of E-banking and the availability of services with easy internet access. Security concerns are significant but vary among customers. Intuitive interfaces and cost savings are less important on average, with more variability in customer preferences for these factors. The study concluded that financial institutions operating in the E-banking sector should prioritize their efforts based on these findings. While security-related challenges have moderate importance with some variation in perceptions, challenges related to repetitional damage, technological advancements, and cost are deemed significantly more critical with relatively uniform opinions among respondents. Addressing these challenges effectively will not only enhance the security and reliability of E-banking systems but also contribute to maintaining a positive reputation and staying competitive in the rapidly evolving digital landscape. Additionally, institutions should be mindful of accessibility concerns and work towards inclusive E-banking services, taking into account the varying levels of importance placed on this challenge by different respondents. The study recommends that the bank should invest in robust online and mobile banking platforms to ensure 24/7 accessibility for the customers. To make sure that the service is available on various devices and browsers to accommodate different customer preferences. Recognize that security concerns vary among customers. Offer customizable security options whenever possible, allowing users to adjust their security settings based on their comfort level.
This is a dissertation.